STRATEGI ADAPTASI MASYARAKAT KAMPUNG JOGOYUDAN YOGYAKARTA TERHADAP BENCANA BANJIR LAHAR DINGIN MERAPI 2010 - , MOCHAMAD AZHAR RIVANY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowadays, urban settlement has an increasing disaster risk. Disaster risk is the potential losses in lives, health status, livelihoods, assets and services, which could occur to a particular community or society over some specified future time period (UNISDR,2009). For example, Kampung Jogoyudan is one of many urban settlement located in flood plain area of Code River, Yogyakarta which has high disaster risk (BPPTKG DIY,2012). In the last flash flood in 2010, that settlement was the most devastated areas in Yogyakarta City. Around 150 houses were damaged, the bridge that connects two settlement was broke, and many other public facilities such as wellspring and public toilet were filthed and damaged. This situation causes a serious disruption which lead the people of Jogoyudan to suffer many losses. Because of that the people of Jogoyudan has done various adaptation strategies due to flash flood. These strategies were adaptation by reaction, by adjustment, by withdrawal, and adaptation by cooperation. The last strategy was the only strategy that implemented in Kampung Jogoyudan (NGO facilitator, Habitat for Humanity, 2013). The People of Jogoyudan rely on the cooperation as a strategy in a recovery phase especially to reconstruct their houses. There is a theory that explained adaptation strategy due to hazard which was issued by Haryadi and Setiawan (2010) and also Berry (1980). The kind of strategy were adaptation by reaction, by adjustment, and adaptation by withdrawal. This theory is called theory of individual adaptation to environmental change. Not all of the strategies done by the people of Jogoyudan can be explained by this theory. There is one strategy that can not be explained yet by this theory that is adaptation by cooperation. Due to difference between the phenomena and theory, the main purpose of this research is to modify the theory. To fulfill the purpose, this research tries to describe adaptation strategies of Jogoyudan people to encounter the hazard and to identify various factor that influence them in choosing adaptation strategy. The method used in this research was qualitative method with case study approach. Then, the analytical techniques which were used in this research were pattern matching, time series analysis, and explanation building. The data were collected by using primary and secondary survey. Primary survey was done by direct observation, participative observation, indepth interview with purposive sampling technique. Based on analytical result cooperation strategy has a common purpose with former adaptation strategy which was issued by Haryadi and Setiawan (2010) and also Berry (1980). This common purpose is to decrease environmental pressure cause by disaster. The difference is the strategy uses social capital owned by the people of Jogoyudan. So that, social capital is identified as a factor that influences the difference. Further analysis result that there are another factor which influence the order of activities done by the people of Jogoyudan to encounter the Hazard. These factors are the absent of contingency planning in settlement level and the characteristic of the hazard.